Rome Precision Solar Photometric Telescope: precision solar full-disk photometry during solar cycles 23–25 - Ermolli, Ilaria; Giorgi, Fabrizio; Chatzistergos, Theodosios (Frontiers in Astronomy and Space Sciences, 2022)
The Rome/PSPT is a ground-based telescope engaged in precision solar photometry. It has a 27-year database of full-disk images of the photosphere and chromosphere beginning in 1996 and continuing to 2022. The solar images have been obtained daily, weather permitting, with approximately 2 arcsec/pixel scale at the \ca line at 393.3 nm, G-band at 430.6 nm, and continuum in the blue and red parts of the spectrum at 409.4 nm and 607.2 nm, respectively. Regular observations were also performed at the green continuum at 535.7 nm for a period of about 18 months. Since the first-light, Rome/PSPT operations have been directed at understanding the source of short-and long-term solar irradiance changes, spanning from one minute to several months, and from one year to a few solar cycles, respectively. However, Rome/PSPT data have also served to study a variety of other topics, including the photometric properties of solar disk features and of the supergranulation manifested by the chromospheric network. Moreover, they have been unique in allowing to bridge series of historical and modern full-disk solar observations, especially as to the \ca line data. Here, we provide an overview of the Rome/PSPT telescope and of the solar monitoring carried out with it from its origin to the present, across solar cycles 23--25. We also briefly describe the main results achieved with Rome/PSPT data, and give an overview of new results being derived with the whole time series of observations covering the period 1996--2022.